Additional list of species of aquatic macrophytes in the lower basin of the Xingu River - DS Abe; C. Sidagis-Galli; T Matsumura-Tundisi; JEM Tundisi; FP Blanco; CRL Faria; JG Tundisi (Brazilian Journal of Biology)
Abstract In this paper the authors present an additional list of aquatic macrophytes in the lower basin of the Xingu River.